1987
DOI: 10.1177/026309238700600101
|View full text |Cite
|
Sign up to set email alerts
|

Annoyance of Audible Infrasound

Abstract: Contours of equal annoyance were determined for pure tones in the frequency range 4 – 31.5 Hz. The curves show a narrowing of the dynamic range of the ear at low frequencies. The same pattern is seen for equal loudness curves, and the results support the theory that the annoyance of infrasound is closely related to the loudness sensation. Annoyance ratings of 1/3 octave noise did not deviate from ratings of pure tones with the same sound pressure level. Combinations of audio and infrasonic noise were in gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 1 publication
5
34
0
1
Order By: Relevance
“…The results obtained in this study indicated that even a small change in sound pressure level above threshold could cause a relatively large change in the annoyance at lower frequencies. Similar results were obtained for frequencies of 31.5 Hz and below by Moller [6] and Adresen and Moller [7]. It was found in this study that a similar trend was observed at frequencies up to 80 Hz.…”
Section: Annoyance Of Pure Tonessupporting
confidence: 91%
See 2 more Smart Citations
“…The results obtained in this study indicated that even a small change in sound pressure level above threshold could cause a relatively large change in the annoyance at lower frequencies. Similar results were obtained for frequencies of 31.5 Hz and below by Moller [6] and Adresen and Moller [7]. It was found in this study that a similar trend was observed at frequencies up to 80 Hz.…”
Section: Annoyance Of Pure Tonessupporting
confidence: 91%
“…This scale is referred to as Graphical Scale in this paper. Moller [6] used a graphical scale to measure annoyance of low frequency tones and concluded that the graphical scale was practicable for comparative measurements. The second scale was a pure tone at 63 Hz: the subjects were asked to adjust its intensity so that it was perceived as equally annoying as the sound under test.…”
Section: Methods Of Annoyance Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The stimuli were presented via Sennheiser HDA200 headphones connected to a PC with MATLAB 2,13 The selection of this duration was based on studies concluding that a stimulus length as short as 30 s can give comparable results to long stimuli. 15,16 Therefore, the standard duration of all stimuli for this study was selected to be equal to 30 s.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…These included neurologic (31,34,41,42,48,49) , cardiac (7,33) , vascular (17,35) and respiratory disorders (10,16,44,45,46) . Lesions of the parotid gland (47) and periodontium of LFN-exposed rats were recently reported (38) .…”
Section: Introductionmentioning
confidence: 99%